CLINICAL PROFILE AND OUTCOME OF COVID-19 PATIENTS: A RETROSPECTIVE OBSERVATIONAL STUDY FROM TERTIARY CARE CENTER IN NORTH INDIA - SK, THAKUR; RAVISHEKAR N, HIREMATH; SK, CHOUDHARY; KULKARNI, MAHESH KRISHNA; PATEL, PRIYANKA; YADAV, NARENDER; GUPTA, SHIVI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: An acute respiratory infection of unknown origin was first detected in Wuhan, China, and reported to the WHO on December 31, 2019, and within a month, this outbreak was declared as a Public Health Emergency of International Concern. This study was carried out with an objective to assess the spectrum of clinical presentations and host-related factors in outcome of COVID-19 during the first wave. Methods: This study was a retrospective observational study on 427 laboratory conformed COVID-19 cases at tertiary care center in North India during 6 months of the first wave. The demographic data, clinical profiles, comorbid conditions, treatment given, duration of hospital stay, and outcome were collected on a predesigned pro forma by the investigator himself and entered a Microsoft Excel sheet and analyzed using SPSS version 17.0 software. Results: Mean age of the study participants was 48.70 years. Majority (34.89%) belonged to above 60 years. About 74% were male. Mean duration of symptoms before detection was 1.30 and mean duration of hospital stay was 11.98 days. Majority had fever (73.54%) followed by myalgia (49.88%). About 85.48% had more than 3 symptoms and 69.32 had symptoms for less than 3 days before getting detected. About 40.52% had comorbidities and only 14.05% had history of contact with COVID confirmed case. Only 8.2% were asymptomatic while 23.19% had severe symptoms. Majority 91.57% were admitted to hospital while only 8.43% were put under home isolation. About 74% were positive on rapid antigen test (RAT) while 29.51% needed RT PCR test to turn positive. About 28.1% had bilateral pneumonia on chest X-ray findings. About 6.3% of were pregnant ladies. The overall mortality rate of our hospital during that 6-month period was 4.69%. Out of all parameters, only age category was statistically significant associated with outcome on discharge while other variables such as comorbidity, symptom duration, and severity of disease during admission did not show any statistically significant association. Conclusion: This single-center study provided the spectrum of clinical presentations and host-related factors in outcome of COVID-19 during the first wave which may help in decrease the burden of disease, minimize social disruption, and reduce the economic impact associated with a pandemic. Early detection, admission, and treatment of individuals with comorbidities and elderly would increase the recovery from the disease, thereby reduce mortality.